Lingkungan Pengendapan Batugamping Berdasarkan Analisis Mikrofasies di Daerah Unsongi Kabupaten Morowali, Provinsi Sulawesi Tengah - Nurhikmah Supardi; Tati Fitriana; Fitrawati A. Marhum; Risqa Permatasyara Mu’min; Agri Debora Singgima (Mataram University, 2026)
The research area is located in Unsongi, East Bungku District, Morowali Regency, Central Sulawesi Province, which is part of the Tokala Formation. Detailed studies of limestone in the Unsongi area have not previously been conducted. This study aims to determine the depositional environment based on microfacies analysis. The research methods included field data collection in the form of outcrop observations, lithological descriptions, and rock sampling. One rock sample was collected from each of the nine observation stations. The samples were subsequently sectioned and subjected to petrographic analysis in the laboratory. Petrographic observations were performed on nine thin sections to identify the detailed rock constituents and determine the Standard Microfacies (SMF). The results indicate that the limestone in the study area consists of crystalline limestone, rudstone, and packstone. These characteristics correspond to SMF 16, 17, and 18. The limestone was deposited in a shallow marine environment with open circulation (open marine/facies zone 7) and in shallow marine settings with restricted circulation (restricted marine/facies zone 8). These facies are characterized by massive lithology, recrystallization, the presence of foraminifera, and gastropod fragments, indicating deposition under relatively high-energy conditions.